Ancient Egyptian book of the moon : coffin texts spells 154-160 - Priskin, Gyula, (Archaeopress Egyptology ;, 2019)
"The Ancient Egyptian Book of the Moon proposes that Coffin Texts spells 154-160, recorded at around the beginning of the 2nd millennium BCE, form the oldest composition about the moon in ancient Egypt and, for that matter, in the entire world. The detailed analysis of these spells, based on a new translation, reveals that they provide a chronologically ordered account of the phenomena of a lunar month. It is argued that through a wide variety of mythological allusions, the separate texts--following an introduction which explains the origins of the month (spell 154)--describe the successive stages of the monthly cycle: the period of invisibility (spell 155), waxing (spell 156), events around the full moon (spell 157), waning (spell 158), the arrival of the last crescent at the eastern horizon (spell 159), and again the conjunction of the sun and the moon when a solar eclipse occurs (spell 160). After highlighting the possible lunar connotations of each spell, further chapters in the book investigate the origins of the composition, its different manuscripts preserved on coffins coming from Hermopolis and Asyut, and the survival of the spells in the later mortuary collection known as the Book of Going Forth by Day."--